Dental Caries Experience, Tooth Loss, and Factors Associated with Unrnet Needs of Haitian Immigrants in New York City - Gustavo D. Cruz, DMD, MPH; Xiaonan Xue, PhD; Racquel Z. LeGeros, PhD; Nandor Halpert, BS; (Blackwell Synergy, 2001)
The aim of this study was to characterize the dental caries experience, tooth loss, and unmet need of a group of Haitian immigrant residents of New York City.